Biossensores para detecção do vírus Epstein-Barr: diagnóstico de fisiopatologias - Balvedi, Renata Pereira Alves (2015)
The Epstein Barr virus (EBV) is studied in this project to establish a latency compared with the infected organism and to a number of pathophysiologies. Its oncogenic potential associated with serological evidence of the presence of the viral agent for cancer and also for autoimmune diseases such as rheumatoid arthritis and lupus erythematosus. Detection processes are necessary and have attracted scientific interest in recent decades, and they are important analytical tools used for clinical diagnosis, disease control, physiological changes, among others. Through the above two genosensors were developed to the specific recognition of EBV by electrochemistry. The peak oxidation of ethidium bromide (EB) in graphite electrodes modified with poly (4-ATP) and the peak tetramethylbenzindine (TMB) reduction, as a new indicator of hybridization oligonucleides, in graphite electrodes modified with poly (AP-4) were designed and evaluated these platforms. Analysis of Surface Plasmon Resonance (SPR) and Atomic Force Microscopy (AFM) were used to complement the study to theoretical and practical application. The prospect of this project is the application in the diagnosis of infection caused by the Epstein-Barr virus (in serum samples, saliva and urine) non-invasively in rapid tests evaluating their sensitivity, selectivity, specificity, speed and low cost.